COMPLEX SOLUTIONS FOR SUSTAINABLE DEVELOPMENT OF DEGRADED LANDS OF THE KHERSON REGION - Radomska, Margaryta; Pavliukh , Lesia; Lyalyuk, Natalia; Petroschuk, Veronika (Proceedings of National Aviation University (archive), 2021)
The sustainable development is the prevailing approach to the use of natural resource potential. The degraded agricultural areas loose their economic value and raise a wide range of environmental concerns. The Kherson region is one of the most overexploited territories in Ukraine, which is characterized by diverse soil-climatic conditions. It was offered to use these lands for cultivation of energy crops. The comparative analysis demonstrated that algae and rapeseed are the most efficient alternatives which are able to complement each other and form a perspective energy mix.